Cryptocurrency Market Volatility and Risk Management During Global Crises: A Systematic Literature Review (2013–2023) - Adekunle, Ahmed Oluwatobi (Yayasan Sinergi Kawula Muda, 2024)
This study investigates cryptocurrency market volatility and its implications for risk management, focusing on its potential as a hedging instrument amid financial uncertainty. A systematic literature review (2013–2023) was conducted to analyze the relationship between cryptocurrency fluctuations, diversification strategies, and regulatory responses, especially during global crises such as the COVID-19 pandemic. External shocks significantly influence price volatility, posing substantial risks to investors. Utilizing a comprehensive literature review, findings reveal that external factors, such as the COVID-19 pandemic, contribute to cryptocurrency price fluctuations, creating significant market uncertainty. Despite its hedging potential, the high volatility of cryptocurrency remains a major risk for investors. Regulatory uncertainty further complicates the adoption of cryptocurrency in financial markets. A well-defined regulatory framework is essential for enhancing investor confidence and fostering market stability. The study highlights the importance of investor education in mitigating cryptocurrency risks, emphasizing the need for financial literacy programs tailored to cryptocurrency investment. Additionally, stablecoins have emerged as a promising solution to address market volatility, providing greater stability compared to other cryptocurrencies. The integration of artificial intelligence and machine learning presents opportunities for improving investment strategies and market predictions. This study suggests that future research should focus on developing predictive models for cryptocurrency price movements and exploring international collaboration on cryptocurrency regulation. By implementing sound risk management strategies, investor education, and regulatory reforms, cryptocurrency can evolve into a more reliable financial asset, contributing to the broader investment landscape.